World history of design - Margolin, Victor 1941- (Bloomsbury Academic, 2015)
"Authored by pre-eminent design scholar Victor Margolin, World History of Design is an indispensable new multi-volume work, providing a comprehensive and detailed historical account of design from prehistory to the end of the twentieth century" -- Provided by publisher.